Hubungan Pengetahuan Bantuan Hidup Dasar (BHD) Dengan Motivasi Pada Polisi Lalu Lintas Dalam Memberikan Pertolongan Pada Korban Kecelakaan Lalu Lintas Di Kota Mageta - Astutik, Nurul Puji; , Arief W. Jadmiko, S.Kep., Ns., M.Kep (2017)
To realize the improving quality of care in the handling of victims or emergency patients required a system for handling victims in an integrated manner and integrated by involving multiple parties. So that the traffic police included in service to the community in the event of traffic accidents due to become the first helper besides masyarakat.Penanganan this accident can hit up to 85% of deaths. Treatment is carried out by basic life support, it is important for the police to have high motivation in helping accident victims with basic life support. The purpose of this study is to determine whether there is a relationship between knowledge of basic life support with the motivation of the traffic police in providing help to the victims of traffic accidents in the city of Magetan. The method used is quantitative descriptive cross-sectional design. Sample was taken using purposivesampling with a sample of 49 respondents. Data were analyzed using descriptive analysis and bivariate analysis usingtest. chi-squareThe results obtained are partly the traffic police in the town of Magetan with knowledge of basic life support in either category (53.1%) and most of the traffic police in the town of Magetan degan motivation to provide relief to the victims of traffic accidents in the category of high motivation (59, 2%). There is a relationship between knowledge of basic life support (BHD) with the motivation of the traffic police in providing help to the victims of traffic accidents in the city of Magetan with the results of P-value of 0.005. Conclusion The results of this study showed the majority of the traffic police have a good knowledge of basic life support and have high motivation in helping the victims of traffic accidents. Keywords: knowledge, motivation, basic life support (BHD), traffic police